2011
DOI: 10.1002/qua.22986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Au(I)–Au(I) closed‐shell attraction on the electronic and phosphorescent properties in a series of coordination compounds: A theoretical study

Abstract: ABSTRACT:The Au(I)-Au(I) closed-shell or aurophilic attraction has been the subject of interest in the experimental and theoretical chemistry fields, due to the intriguing properties associated to it. The presence of phosphorescence in ''aurophilic'' compounds has been addressed to a wide range of applications, but it has not yet been fully understood. A theoretical study on the electronic and phosphorescent properties of the following series of dinuclear gold complexes has been performed: [Au 2 (dmpm) (i-mnt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…That is, there is an order of magnitude increase in interaction from the open form to the benzene‐linked twisted form, and another order of magnitude increase to the pyridine and pyrazine linked twisted forms. The WBIs are consistent with previously reported WBIs for aurophilic Au I interactions . For the open conformation of all complexes, the electronic configurations are all 5d 9.61 6s 1.01 6p 0.12 , while for the twisted form of the benzene linked complex, the electronic configuration is the same as the open forms.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…That is, there is an order of magnitude increase in interaction from the open form to the benzene‐linked twisted form, and another order of magnitude increase to the pyridine and pyrazine linked twisted forms. The WBIs are consistent with previously reported WBIs for aurophilic Au I interactions . For the open conformation of all complexes, the electronic configurations are all 5d 9.61 6s 1.01 6p 0.12 , while for the twisted form of the benzene linked complex, the electronic configuration is the same as the open forms.…”
Section: Resultssupporting
confidence: 90%
“…The WBIs are consistent with previously reported WBIs for aurophilic Au I interactions. [26] For the open conformation of all complexes, the electronic configurations are all 5d 9.61 6s 1.01 6p 0.12 , while for the twisted form of the benzene linked complex, the electronic configuration is the same as the open forms. For the twisted form of the pyridine and pyrazine linked complexes, the electronic configuration is 5d 9.60 6s 0.94 6p 0.20 .…”
Section: Theoretical Calculationsmentioning
confidence: 81%
“…There is only a slight positive charge on all of the group 11 metal centers (NPA average of 0.26–0.40, Table ), which results in a breaking of the formal 5d 10 6s 0 electronic structure of the metal centers. Previously it has been shown that metalophilic bonding is produced by hybridization among the filled 5d shell and the empty 6s and 6p orbitals at the metal center . That is, the greater the population of the 6p orbital, the greater the degree of hybridization and the stronger the metalophilic interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The role of Au(I)‐Au(I) closed‐shell attractions on the electronic and phosphorescent characteristics of a series of related complexes has been thoroughly discussed separately by the groups of Muñiz and Mendizabal, showing the correlation between the strength of the Au(I)‐Au(I) interaction and their phosphorescent attributes …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…role of Au(I)-Au(I) closed-shell attractions on the electronic and phosphorescent characteristics of a series of related complexes has been thoroughly discussed separately by the groups of Muñiz and Mendizabal, showing the correlation between the strength of the Au(I)-Au (I) interaction and their phosphorescent attributes [99][100][101]. A similar behavior where the metal-metal interactions plays a relevant role in the phosphorescence is found in Au(I)-Ag(I) metallophilic attractions and luminescence of [Au 2 (carb) 2 Ag(mu-3,5-Ph 2 pz)] (with Ph = phenyl, pz = pyrazolate) and [Au(im)CH 3 (pz)Ag 2 (mu-3,5-H 2 pz) 2 ] (with im = imidazole) complexes.…”
mentioning
confidence: 99%